MENGAPA INDIVIDU ENGGAN MENCARI PERTOLONGAN MEDIS? SEBUAH TINJAUAN LITERATUR NARATIF - Ervan, Fidela Narasyah (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2024)
Medical care avoidance and medical care delay (i.e., evading and postponing medical care) are serious problems that may lead to fatal consequences. To reduce the prevalence of medical care avoidance and delay in our community, the things contributing to such behaviors must be highlighted. This research was conducted in the form of a narrative literature review, discussing factors that could motivate individuals to put off or avoid medical care. A narrative approach is flexible and interpretive in nature. Three databases were used in this review: PubMed, SpringerLink, and Web of Science; the search was conducted in August 2024. After the sources had been reviewed, the factors that perpetuated medical care avoidance and delay were categorized into three groups: (1) psychological/personal factors, (2) social/interpersonal factors, and (3) structural/organizational factors. Examples of psychological factors included fear and shame; an instance of social factors was perceived problems with the doctor; and an example of structural factors was high cost. In order to encourage members of our community to seek medical help in a timely fashion, these factors must be addressed and overcome with precision.